Viral nervous necrosis in gilthead sea bream (Sparus aurata) caused by reassortant betanodavirus RGNNV/SJNNV: an emerging threat for Mediterranean aquaculture - Toffan, Anna (Sci Rep, 2017)
Viral nervous necrosis (VNN) certainly represents the biggest challenge for the sustainability and the development of aquaculture. A large number of economically relevant fish species have proven to be susceptible to the disease. Conversely, gilthead sea bream has generally been considered resistant to VNN, although it has been possible to isolate the virus from apparently healthy sea bream and sporadically from affected larvae and postlarvae. Unexpectedly, in 2014–2016 an increasing number of hatcheries in Europe have experienced mass mortalities in sea bream larvae. Two clinical outbreaks were monitored over this time span and findings are reported in this paper. Despite showing no specific clinical signs, the affected fish displayed high mortality and histological lesions typical of VNN. Fish tested positive for betanodavirus by different laboratory techniques. The isolates were all genetically characterized as being reassortant strains RGNNV/SJNNV. A genetic characterization of all sea bream betanodaviruses which had been isolated in the past had revealed that the majority of the strains infecting sea bream are actually RGNNV/SJNNV. Taken together, this information strongly suggests that RGNNV/SJNNV betanodavirus possesses a particular tropism to sea bream, which can pose a new and unexpected threat to the Mediterranean aquaculture.